PENGARUH PENGGUNAAN MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE GROUP INVESTIGATION (GI) TERHADAP HASIL BELAJAR IPS TERPADU SMP MUHAMMADIYAH 1 METRO - Yesi Budiarti (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
The background is the number of students who have not yet reached the KKM score or have not yet completed the learning results of the Integrated Ips Class VIIIB in the even semester of Muhammadiyah Middle School 1 Metro 2017/2018 Academic Year. In connection with these problems, the formulation of the problem is